Consumption of plastic bottles and cups at road breakfasts new behavior guidelines Lima 2019-2020 - Jurado Falconi, Eulalia (2021)
The greatest risk is not in the consumption of plastic but is the management of single-use plastic waste, there is a socially accepted behavior of not valuing recycling or reuse, The objective was to analyze the relationship between behavior patterns in consumption of food with the single-use plastic bottles and cups in the cart breakfast trade. Surveys were applied to students from different universities, vendors of wheelbarrow breakfasts. Breakfast is still accessible and affordable for the popular economy. The pandemic accelerated changes in the economy and social life of sellers and consumers that modified safety and hygiene measures. The plastic bottle trade is in a process of expansion and its replacement is not perceived in the short term. There is an important sector of the population that has the perception that the use of plastic is safe, the belief that plastic is a non-substitutable product is cheaper to use and dispose of than to refuse, recycle. There are no explicit or tacit rules on the management of the final disposal of single-use plastic articles. It is recommended, Awareness of society including companies and explicit regulations to promote recycling behaviors and reuse of single-use plastic bottles.